2015
DOI: 10.17219/acem/40456
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgery on the Efficacy of Adjuvant Therapy in Glioblastoma Multiforme

Abstract: Background. Glioblastoma multiforme (GBM) is the most malignant brain tumor. Surgery still remains a fundamental part of treatment in GBM, followed by radiotherapy and chemotherapy. Objectives. The aim of the study was to assess the impact of surgery on the efficacy of adjuvant therapy in patients with glioblastoma multiforme. Material and Methods. The study involved 181 patients: 50 treated with adjuvant radiotherapy (RTH) only (60 Gy in daily 2Gy fractions) and 131 treated with postoperative radiochemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…To date, most patients with glioma receive combined therapy with little efficacy (2). Since GSCs are responsible for tumor maintenance, recurrence and resistance to conventional treatments, therapy targeting NEAT1 may hold great promise for glioma treatment (5,26). In the present study, we found that GSCs had higher NEAT1 levels than the relative differentiated cells.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…To date, most patients with glioma receive combined therapy with little efficacy (2). Since GSCs are responsible for tumor maintenance, recurrence and resistance to conventional treatments, therapy targeting NEAT1 may hold great promise for glioma treatment (5,26). In the present study, we found that GSCs had higher NEAT1 levels than the relative differentiated cells.…”
Section: Discussionsupporting
confidence: 56%
“…Glioma is a highly fatal disease and a major contributor to death in patients with central nervous system tumors (2,3,5,26). Glioma is asymptomatic in the early stage and is generally detected with extensive invasion into adjacent normal brain tissue (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors other than treatment received are thought to affect survival of patients with HGG, such as performance status, age and supportive care . In addition, there has been interest in whether the extent of tumour resection and waiting time between surgery and the start of RT could influence patients outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the primary therapeutic modality for pilocytic astrocytomas and other LGGs. [17][18][19][20][21] Gross total resection (GTR) is often curative, despite the presence of residual microscopic disease. Clinical management strategies of children with subtotal resections are typically developed at a multidisciplinary pediatric neuro-oncology tumor board on a case-by-case basis.…”
Section: Introductionmentioning
confidence: 99%